Aktualisasi Peran Sosial Wanita Cina di Jabodetabek - Muas, R. Tuty Nur Mutia; Witanto, Eddy Prabowo (UI Scholars Hub, 2005)
Actualization Of Chinese Women’s Social Role In Jabodetabek. This research is based on a primary question